The blast-induced noise and ground vibration structural and human response: A case for the South African mud house homes - X. Gumede (The Southern African Institute of Mining and Metallurgy, 2025)
Mud houses are common structures in most South African rural homes closer to the mining operations. Fulltime dwellers in these properties are often the elderly. The mine codes of practice and the South African legislative instruments attempt to define the damage criteria to limit the effect of the blast-induced noise and ground vibrations to different structures. All these assessment criteria are based on the peak particle velocity and noise generated during blasting. The South African safe limit criterion that was adopted was initially derived from the international standards, which were then used as a local guideline. This paper evaluates the currently adopted safe limit criteria used in South Africa for a mud house, currently rated at 6 mm per second and 120 decibels to134 decibels, for blast-induced seismicity and noise, respectively. Further, a study was performed on a residential house near a coal mine (5.26 km) based in Mpumalanga following numerous complaints by the owner, launched at the mine and to the Department of Minerals and Petroleum Resources. The aim of the study was to measure the magnitude of blast-induced triggers experienced at the aggrieved homestead and to establish if there is a likelihood that an irritation or damage may be caused by these triggers. The seismometer was installed at about 2 m from the mudhouse, from 1 July 2022 to 31 of July 2022. Five blast-induced triggers were recorded during the period showing an average of 0.09 mm/s and 121 decibels for blast-induced seismicity and noise, respectively. The results obtained indicated a maximum seismicity of 0.15 mm/s. This seismicity was below the perceptible vibrations obtained from daily home activities such as walking, jumping, and door slamming, which produce 0.8 mm/s, 7.1 mm/s, and 12.7 mm/s, respectively. Seismicity was therefore not likely to have caused any annoyance and or damage. For noise, the results indicated a maximum of 123 decibels and an average of 121 decibels from five events recorded. A literature review suggests that slight damage may occur when airblast frequencies match the natural frequencies of structures at 120 decibels. Based on these results, it can be concluded, therefore, that the noise, rather than seismicity, is more likely to be the cause of damage to the structure assessed. For improvement, a new approach is proposed based on relating the safe limits to the structural and human response.